Reliability of Malayalam version of Geriatric Oral Health Assessment Index among institutionalized elderly in Alleppey, Kerala (India): A pilot study - Kuldeep Singh Shekhawat; Arunima Chauhan; Anitha Ann Koshy; P Rekha; Hemanth Kumar (Wolters Kluwer Medknow Publications, 2016)
Background: Oral health has a profound effect on the daily activities of geriatric group. India being a multilingual country, it is essential that instruments used to evaluate the quality of life is in local languages. However, the validation and translational aspect are important before involving a larger cohort of geriatrics. Aim: To assess the reliability of Malayalam version of Geriatric Oral Health Assessment Index (GOHAI-m). Settings and Design: Institutionalized elderly in Alleppey, Kerala, cross-sectional study. Materials and Methods: The 12 items in GOHAI were translated into Malayalam using a back-translation technique. The comprehensibility of the Malayalam version was assessed by a pilot study. Fifty institutionalized elderly answered the questionnaire. Impact based on age and marital status was also assessed. Statistical Analysis: Independent sample t-test, Cronbach's alpha, test-retest reliability using intraclass correlation coefficient (ICC). Results: The mean GOHAI-m scores were higher for elderly participants with slightly more impact on quality of life such as for biting or chewing food, and lower mean GOHAI-m scores indicated a positive impact on quality of life such as their self-conscious of oral health. Cronbach's alpha of 0.677 was reached with 12 items. Item 12 had a negative item-total correlation, −0.016, the deletion of Item-12 increased the item correlation to 0.7. Test-retest reliability of 0.65 for ICC indicated moderate stability. Females had more impact than males (P < 0.05). Age and marital status had no impact on their quality of life. Conclusion: The primary analysis of GOHAI-m indicated moderate stability. The elimination of negative items depends on the objectives of the study and/or after conducting a larger study keeping in view various parameters of the study.